Handbook of cultural intelligence : theory, measurement, and applications - Ang, Soon; Van Dyne, Linn, 1949- (Routledge, 2015)
With contributions from eminent scholars worldwide, this handbook is a state-of-the-science summary of the body of knowledge about cultural intelligence--an individual's ability to function effectively in situations characterized by cultural diversity--and its relevance for managing diversity both within and across cultures.